Bathing suit ichthyosis: a temperature sensitive phenotype. - Oji, V.; Ahvazi, B.; Hausser, I.; Hennies, H.C.; Jacyk, W.K.; Aufenvenne, K.; Traupe, H. (European Journal of Pediatric Dermatology, 2008)
Bathing suit ichthyosis: a temperature sensitive phenotype. Bathing suit ichthyosis is a particular phenotype of congenital non bullous ichthyosis due to mutations in transglutaminase-1 gene and clinically characterized by lach of limb involvement. This peculiar phenotype is due to the activity of its causing mutations that directly or indirectly can make the transglutaminase-1 enzyme sensitive to the changes of the skin temperature.